2006
DOI: 10.1002/mnfr.200600173
|View full text |Cite
|
Sign up to set email alerts
|

Overview of antibacterial, antitoxin, antiviral, and antifungal activities of tea flavonoids and teas

Abstract: Tea leaves produce organic compounds that may be involved in the defense of the plants against invading pathogens including insects, bacteria, fungi, and viruses. These metabolites include polyphenolic compounds, the six so-called catechins, and the methyl-xanthine alkaloids caffeine, theobromine, and theophylline. Postharvest inactivation of phenol oxidases in green tea leaves prevents oxidation of the catechins, whereas postharvest enzyme-catalyzed oxidation (fermentation) of catechins in tea leaves results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
385
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(400 citation statements)
references
References 140 publications
9
385
0
6
Order By: Relevance
“…As the most abundant catechin, making up more than half of green www.nature.com/aps Ling JX et al Acta Pharmacologica Sinica npg tea polyphenols, epigallocatechin gallate (EGCG) accounts for the majority of the potential health benefits brought about by green tea consumption. Extensive laboratory and communitybased epidemiological studies have described a wide range of actions of EGCG, including antioxidant, antiallergic, antibacterial, antitumor and antiviral activities [12] . However, the mechanisms of action of EGCG against FluA, such as whether EGCG acts directly on molecular components of the virus or upon cellular events necessary for the viral life cycle, remain incompletely defined.…”
Section: Introductionmentioning
confidence: 99%
“…As the most abundant catechin, making up more than half of green www.nature.com/aps Ling JX et al Acta Pharmacologica Sinica npg tea polyphenols, epigallocatechin gallate (EGCG) accounts for the majority of the potential health benefits brought about by green tea consumption. Extensive laboratory and communitybased epidemiological studies have described a wide range of actions of EGCG, including antioxidant, antiallergic, antibacterial, antitumor and antiviral activities [12] . However, the mechanisms of action of EGCG against FluA, such as whether EGCG acts directly on molecular components of the virus or upon cellular events necessary for the viral life cycle, remain incompletely defined.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty one prenyl flavonoid glycosides and eighteen phenolic acids were identified or tentatively identified using the Q-TOF-MS, and an ethylene glycol (Click OEG) column by Wang (2010). Flavonoids was one of the most important contents of Epimedium and it had been shown to display a number of biological activities such as antioxidant (Giovannini et al 2006;Sang et al 2005) antiviral, antifungal (Friedman 2007), anticancerous (Li et al 2007;Fresco et al 2006) antiangiogenic (Oak et al 2005) and anti-inflammatory activities (Dryden et al 2006). Icariin (C 33 H 40 O 15 ; molecular weight: 676.67, ICA) was one of the main flavonoids of Epimedium koreanum Nakai and it was always used as the standard for the quality control of Epimedium related remedies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have shown that flavonoids contribute to the overall antioxidant capacity in vivo [4][5]. Besides their antioxidant activity, both flavonoid aglycones and glycosides can act as antifungal, insect antifeedants, antimicrobials and antivirals and anti-inflammatory, and are also of particular importance in chemotaxonomy [6][7][8]. Associated with this, their identification in numerous herbs and infusions has also been the focus of several groups worldwide, particularly from regions where traditional medicine plays an important role [9,10].…”
Section: Introductionmentioning
confidence: 99%